Small bowel enterocyte abnormalities caused by methotrexate treatment in acute lymphoblastic leukaemia of childhood. Issue 7 (July 1981) - Gwavava, N J; Pinkerton, C R; Glasgow, J F; Sloan, J M; Bridges, J M
Abstract : Jejunal biopsy specimens from 10 children with acute lymphoblastic leukaemia on methotrexate treatment were compared with 10 from children being investigated for diarrhoea or failure to thrive. In association with methotrexate treatment on both light and electron microscopy, there were marked morphological abnormalities in the villus enterocytes. These consisted of a striking distention of the lateral basal intercellular spaces, cell vacuolation and patchy necrosis and was most marked when methotrexate treatment was given between 24 and 72 h before biopsy. Two mechanisms may be involved: an early direct toxic effect on the mature enterocyte coupled with interference with crypt cell generation, possibly causing ageing and loss of cells proximal to the normal extrusion zone. These pathological changes may account for the malabsorption in association with methotrexate treatment.